PENGARUH SUBSTITUSI SERBUK ECENG GONDOK DAN AMPAS TEMPE TERHADAP PRODUKSI JAMUR TIRAM PUTIH (Pleurotus ostreatus) - Syiwi Ratri Indriyani; Rommy Andhika Laksono; Kasdi Pirngadi (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2021)
In general, the basic material used in the planting media of white oyster mushroom is sawdust. The increasing need for sawdust, without being offset by sufficient availability will make sawdust difficult to obtain. The research aimed to obtain the composition substitution of the hyacinth powder and tempe dregs which provided the highest results for growth and yield of white oyster mushroom (Pleurotus ostreatus). The research was conducted in Gintung Kerta Village, Klari Subdistrict, Karawang District, West Java from July 2020 to October 2020. The method used was an experimental method with used Randomized Block Design (RDB) single factor, consisting of 9 treatments and 3 replications so there were 27 experimental units. The treatments were: A (without the addition of growing media treatment); B (5% water hyacinth powder); C (10% water hyacinth powder); D (15% water hyacinth powder; E (20% water hyacinth powder); F (Tempe dregs 5%); G (Tempe dregs 10%); H (Tempe dregs 15%); and I (Tempe dregs 20%). The results showed that there was a significant effect of composition proportion substitution of the hyacinth powder and tempe dregs on the length of mycelium per baglog, maximum fruit hood diameter per baglog, harvest intensity per baglog, fresh weight of mushrooms per baglog, and total yield in a planting period. The treatment of H (Tempe dregs 15%) gave the highest yield to the harvest intensity of 2.44 times, the mushroom fresh weight of 89.42 g/baglog, and the total yield in a planting period of 408.00 g.